"Beyond Romance : exploring identity and transformation in Penelope and Colin's journey in Bridgerton" - Moschini, Ailén Naomi (My University, 2024)
This thesis explores the character development and relationship dynamics of Penelope Featherington and Colin Bridgerton in the third season of Netflix's Bridgerton, employing Jungian psychology, Joseph Campbell’s Hero’s Journey, and Maureen Murdock’s Heroine’s Journey as theoretical frameworks. The research addresses the question: How do the processes of individuation, the Hero’s Journey, and the Heroine’s Journey manifest in the character development and relationship dynamics of Penelope and Colin? The hypothesis posits that these processes shape the characters' psychological growth, leading to their mutual integration and self-realization. Using a systematic content analysis of key scenes, this study examines how psychological and archetypal motifs guide character development. Penelope’s transformation is analyzed through Murdock’s Heroine’s Journey, focusing on her reclamation of feminine power, while Colin’s journey is framed by Campbell’s monomyth, emphasizing his integration of shadow aspects and evolving masculinity. Findings demonstrate that Penelope and Colin’s character arcs align with archetypal narratives while engaging with themes of gender, identity, and societal norms within a historical romance setting. This thesis contributes to media studies by presenting a model for character analysis in television, offering insights into how archetypal storytelling enhances emotional engagement with audiences, and enriching our understanding of character dynamics in contemporary media.
Keywords: Bridgerton; Jungian psychology; Hero’s journey; Heroine’s journey; Carl Jung; Individuation; Archetypes; Character development; Media studies; Gender dynamics